2012
DOI: 10.1007/s13280-012-0313-2
|View full text |Cite
|
Sign up to set email alerts
|

Treelines Will be Understood Once the Functional Difference Between a Tree and a Shrub Is

Abstract: Trees are taller than shrubs, grasses, and herbs. What is the disadvantage of being tall so that trees are restricted to warmer regions than low stature life forms? This article offers a brief review of the current state of biological treeline theory, and then explores the significance of tallness from a carbon balance, freezing resistance, and microclimatological perspective. It will be argued that having of a woody stem is neither a burden to the carbon balance nor does it add to the risk of freezing damage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 46 publications
2
100
0
2
Order By: Relevance
“…Beyond 1900 m a.s.l., trees become more stunted to create a more suitable microclime in order to survive. The stature of multiple tree species in several prominent mountain ranges was also found to become dramatically stunted across a relatively small altitudinal range of only 50 to 100 m below the treeline [26,27]. These results suggest that tree stature change is much faster or even abrupt in the alpine treeline ecotone or close to the alpine treeline.…”
Section: Stature Of Birch Growing Along An Altitudinal Gradientmentioning
confidence: 78%
See 2 more Smart Citations
“…Beyond 1900 m a.s.l., trees become more stunted to create a more suitable microclime in order to survive. The stature of multiple tree species in several prominent mountain ranges was also found to become dramatically stunted across a relatively small altitudinal range of only 50 to 100 m below the treeline [26,27]. These results suggest that tree stature change is much faster or even abrupt in the alpine treeline ecotone or close to the alpine treeline.…”
Section: Stature Of Birch Growing Along An Altitudinal Gradientmentioning
confidence: 78%
“…on Changbai Mountain (see Table S2 in Supplementary Materials). It has been reported that when soil temperature is lower than 5 • C, a very small reduction in soil temperature may lead to a dramatic increase in the time required for mitotic division of plant cells and a doubling in the time needed for cell reproduction [27]. Moreover, resource allocation from storage tissues to a tree's apical meristems (height growth) yields a relatively lower reward relative to xylem (radial growth) due to the longer transport pathway [28].…”
Section: Stature Of Birch Growing Along An Altitudinal Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…Signs of upward treeline and timberline shifts have already been detected in several decadal-scale studies (Harsch et al, 2009;Heiri et al, 2014;Körner, 2012b;Theurillat and Guisan, 2001;Tinner and Ammann, 2005), supporting predictions that ongoing global warming leads to rises in treeline and timberline with corresponding reductions in alpine grassland .…”
Section: Introductionmentioning
confidence: 75%
“…Hence, this special issue presents papers on monitoring Hedenås et al 2012;Körner 2012;Christensen et al 2012), on manipulations (Michelsen et al 2012;Cornelissen et al 2012;Bokhorst et al 2012;Gwynn-Jones et al 2012;Keuper et al 2012), and finally, papers on modeling (Miller and Smith 2012;Yang et al 2012;Hein et al 2012). Fig.…”
Section: This Special Reportmentioning
confidence: 99%